Treatment of lesions on the vestibular surfaces of permanent teeth with the use of liquid resin of low viscosity - Szewczak, Ilona; Kubić-Filiks, Beata; Szymańska, Jolanta (Polish Journal of Public Health, 2020)
One of the methods of treatment of initial stages of dental caries, lesions characterized by demineralization, and white spots on the vestibular surfaces of permanent teeth, is infiltration with liquid resin of low viscosity. It is a non-invasive method which is worth recommending and popularizing among patients. On the basis of available literature the therapeutic method of infiltration with liquid resin of low viscosity is presented. The use of resin of low viscosity allows for obtaining appropriate esthetic and functional appearance of teeth, which is a vital step in improvement of quality of social and professional life of patient.